2002
DOI: 10.1176/appi.ajp.159.4.585
|View full text |Cite
|
Sign up to set email alerts
|

Views of Potential Subjects Toward Proposed Regulations for Clinical Research With Adults Unable to Consent

Abstract: Enrolling individuals who are unable to consent in research that offers no potential for medical benefit is consistent with the preferences of at least some individuals. This suggests that such research should not be prohibited, provided there is sufficient evidence that it is consistent with the preferences of individual subjects. Requiring that such evidence be provided in a formal research advance directive may be unnecessarily restrictive. More research is needed to assess whether the findings in this grou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
70
1

Year Published

2004
2004
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(74 citation statements)
references
References 17 publications
3
70
1
Order By: Relevance
“…Several factors contributed to emotional distress: observing a loved one in a critically ill state, grappling with uncertainty regarding which institutional review boards (IRBs) apply such protections, explored the views of individuals regard ing substituted judgment for research of chronic diseases, and looked at the emotional impact of functioning as an SDM in the ICU setting. 7,10,[13][14][15][16][17][18][19] We undertook the current investigation to further study how the pressures and concerns of serving as SDM for an acutely ill family member might infl uence attitudes regarding clinical research and how this information might be used to enhance the consent process.…”
Section: Focus Group Findingsmentioning
confidence: 99%
“…Several factors contributed to emotional distress: observing a loved one in a critically ill state, grappling with uncertainty regarding which institutional review boards (IRBs) apply such protections, explored the views of individuals regard ing substituted judgment for research of chronic diseases, and looked at the emotional impact of functioning as an SDM in the ICU setting. 7,10,[13][14][15][16][17][18][19] We undertook the current investigation to further study how the pressures and concerns of serving as SDM for an acutely ill family member might infl uence attitudes regarding clinical research and how this information might be used to enhance the consent process.…”
Section: Focus Group Findingsmentioning
confidence: 99%
“…(1214, 26) Among our participants, we found that the older general public strongly supports a policy of surrogate consent for dementia research and that this support increased after in-depth education and peer deliberation; for example, at baseline, support for a policy of surrogate consent for a dementia research protocol involving gene transfer neurosurgery increased from 56% to 68% after deliberation. (22) Our thematic analysis of participants’ deliberations provides important insights into what this overall support means.…”
Section: Discussionmentioning
confidence: 85%
“…(1215) But most of these studies have been traditional cross-sectional surveys and do not provide insights into the underlying basis for these opinions. Given the historical, ethical, and scientific complexities of the topic, understanding the underlying reasons for such opinions would provide insights into their validity.…”
mentioning
confidence: 99%
“…Surveys of potential research participants can give useful data that is distinct from any conclusions that can be drawn from the fact that patients do in fact enroll in research studies. 49 Surveys of IRB members or scientists and scientific administrators regarding how they apply the risk-benefit analysis regulations can also illuminate how policies may in fact get applied. 50 Surveys of the general public on the appropriateness of certain implied tradeoffs in research protocols can also inform the debate.…”
Section: Favorable Risk-benefit Ratiomentioning
confidence: 99%